Professores / pesquisadores da pós-graduação em botânica no Brasil: análises métricas de produtividade - Amarante, Cristiana Maria Vasconcellos Goulart do (2011)
Exploratory research of scientific productivity of professors/researchers of Botany doctorate courses in Brazil using bibliometrics methods anchored in Scientific Communication. Sixteen Botany doctorate courses were identified; retrieved data on these courses refer to promoting institutions, concentration areas, research lines, and Cape's grades all data leading to professors/researchers target of this research. Special attention was paid to productivity patterns of the elite along the time period as well as their citation numbers. Bibliometrics methods and techniques used include Elitism Law, citation analysis, impact factor and h-index. The Elite consists of 18 professors/researchers linked to the following public institutions: UFV, UFRPE, IBT, UFRJ, UNESP, USP, UEFS, UFMG, UNB, UFPE and UNICAMP in the areas of Botany, Agronomics, Ecology, Chemistry, Forestry and Engineering Resources, Pharmaceutics, Genetics, Environmental Sciences, Geosciences, Microbiology and Anthropology reflecting the interdisciplinary character of the area itself. Geographical concentration of courses points to the Southeast region, especially the state of São Paulo, which obtained the highest Cape's grades. Professors/Researchers productivity amounts to 2.489 papers, published in 521 journals Brazilian and foreign, with an expressive increase of these latter in recent years, the Web of Science citation analysis of the elite shows an expressive number of indexed and cited papers. The Impact factor of journals where the elite publishes shows the elite s tendency to publish in journals of very large impact factor, such as the journal Nature - an excellence journal. This research identified few former Bibliometrics studies in Botany which adds to its relevance and opportunity